1997
DOI: 10.1093/ajcn/65.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and cognitive functioning in a normally aging sample: a 6-y reassessment

Abstract: Associations between nutritional status and cognitive performance were examined in 137 elderly (aged 66-90 y) community residents. Participants were well-educated, adequately nourished, and free of significant cognitive impairment. Performance on cognitive tests in 1986 was related to both past (1980) and concurrent (1986) nutritional status. Several significant associations (P < 0.05) were observed between cognition and concurrent vitamin status, including better abstraction performance with higher biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(119 citation statements)
references
References 24 publications
8
110
1
Order By: Relevance
“…Importantly, we found that learning performances are also directly affected by diet, thereby adding a new dimension to the fitness landscape of D. melanogaster larvae. The effects of malnutrition on cognitive performances have long been identified in mammals (La Rue et al, 1997) and insects [e.g. honeybees (Arien et al, 2015;Wright et al, 2013) and Drosophila (Guo et al, 1996;Kawecki, 2010;Kolss and Kawecki, 2008;Shou-Zhen et al, 1997)], and may be due to modifications of the biochemical composition of the brain, developmental procedures (Heisenberg et al, 1995;Xia et al, 1997) or sensorial modalities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we found that learning performances are also directly affected by diet, thereby adding a new dimension to the fitness landscape of D. melanogaster larvae. The effects of malnutrition on cognitive performances have long been identified in mammals (La Rue et al, 1997) and insects [e.g. honeybees (Arien et al, 2015;Wright et al, 2013) and Drosophila (Guo et al, 1996;Kawecki, 2010;Kolss and Kawecki, 2008;Shou-Zhen et al, 1997)], and may be due to modifications of the biochemical composition of the brain, developmental procedures (Heisenberg et al, 1995;Xia et al, 1997) or sensorial modalities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly subjects with low serum folate and B 12 concentrations have impaired spatial copying skills (52) and abstraction performance (53), and score worse on tests of nonverbal abstract thinking when compared with age-matched individuals with high serum folate and B 12 concentrations (54). Folate-deficient mice also display behavioral abnormalities (55).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have found that poor performance on some cognitive tests has been associated with low vitamin nutriture, e.g., low serum levels of vitamin B 12 , ascorbate, riboflavin, and folate [4][5][6]13]. In our study, cognitive malfunction was manifest even when the elderly were not vitamin deficient ( vitamin-unsupplemented group after 1 year (see Results, table 2), further deterioration of their initial cognitive malfunctioning score failed to markedly occur (table 2 -MMSE).…”
Section: Discussionmentioning
confidence: 99%